Cytotoxicity of BSA‐Stabilized Gold Nanoclusters: In Vitro and In Vivo Study. Issue 21 (28th January 2015) - Dong, Liyun; Li, Mulin; Zhang, Song; Li, Jun; Shen, Guanxin; Tu, Yating; Zhu, Jintao; Tao, Juan
<x xml:space="preserve">Abstract</x> Gold nanoclusters (Au NCs) are one of the most promising fluorescent nanomaterials for bioimaging, targeting, and cancer therapy due to their tunable optical properties, yet their biocompatibility still remains unclear. Herein, the cytotoxicity of bovine serum albumin (BSA)‐stabilized Au NCs is studied by using three tumor cell lines and two normal cell lines. The results indicate that Au NCs induce the decline of cell viabilities of different cell lines to varying degrees in a dose‐ and time‐dependent manner, and umbilical vein endothelial cells which had a higher intake of Au NCs than melanoma cells show more toxicity. Addition of free BSA to BSA‐Au NCs solutions can relieve the cytotoxicity, implying that BSA can prevent cell damage. Moreover, Au NCs increase intracellular reactive oxygen species (ROS) production, further causing cell apoptosis. Furthermore, N‐acetylcysteine, a ROS scavenger, partially reverses Au NCs‐induced cell apoptosis and cytotoxicity, indicating that ROS might be one of the primary reasons for the toxicity of BSA‐Au NCs. Surprisingly, Au NCs with concentrations of 5 and 20 nM significantly inhibit tumor growth in the xenograft mice model of human liver cancer, which might provide a new avenue for the design of anti‐cancer drug delivery vehicles.